Nuclear Power Plant to Support Indonesia's Net Zero Emissions: A Case Study of Small Modular Reactor Technology Selection Using Technology Readiness Level and Levelized Cost of Electricity Comparing Method - Rahmanta, Mujammil Asdhiyoga (MDPI, 2023)
Most power plants, particularly those that burn fossil fuels such as coal, oil, and gas, create CO2, a greenhouse gas that contributes to climate change. By 2060, the Indonesian government has committed to reach net zero emissions. With the lowest CO2 emissions, nuclear power plants are dependable sources of energy. Small modular reactors (SMRs) are a particular kind of nuclear power plant that has the potential to be Indonesia's first commercial nuclear power plant because of their small size, low capacity, uncomplicated design, and modular characteristics. The purpose of this study is to examine the economics and technological feasibility of SMRs. In this analysis, the levelized cost of electricity (LCOE) comparative method and the technology readiness level (TRL) approach are both applied. The SMRs with a minimum TRL value of 7 were CAREM-25 (TRL7), KLT-40S (TRL8), and HTR-PM (TRL 8), according to the results of this research. Although CAREM-25 and KLT-40S are still in the demonstration stage and have not yet entered the market, their LCOE estimates are greater than 0.07 USD/kWh with a 5% discount rate. Whereas CAREM 100 MW is an economy scale from CAREM-25 and VBER 300 MW is a commercial size from KLT-40S, HTR-PM is already an economy scale. With discount rates between 5% and 10%, the LCOE values of HTR-PM, CAREM 100 MW, and VBER 300 MW range from 0.06 USD to 0.12 USD per kWh. Other than hydropower and coal-fired power plants, these LCOE figures can compete with the local LCOE in Indonesia and the LCOE of a variety of other types of power plants.